Protecting the Rights of War Crimes Victims: Determining Ways to Prevent Their Secondary Victimization - Spitsyna, Hanna; Iemets, Ivan (Archives of Criminology and Forensic Sciences, 2024)
The modern conditions of our state’s development, including the geopolitical situation and the state of the security environment, highlight the need to enhance the efficiency of law enforcement agencies, ensure effective resistance to war crimes and criminal offenses associated with war. At the same time, it is necessary to ensure the protection and restoration of the rights of affected individuals. In view of the above, the Article Purpose is formulated as defining and characterizing the specifics of protecting the rights of victims of war crimes and war-related criminal offenses, as well as developing guidelines to enhance the efficiency of this activity. It is argued that, at present, legal theory has neither formulated definitions of the concepts of “war crimes” and “war-related criminal offenses” nor identified the specific types of crimes directly related to this group. Ways of reforming the provisions of the current criminal procedural legislation are outlined, taking into account the need to protect victims of war crimes and prevent instances of their secondary victimization.